Status of Accredited Collages of Education in selected schools in NCR & Laguna: an assessment - Avelino, Ramon L.; Palines, Godelia A.; Esteban, Angelita M. (Parañaque City: Olivarez College, 1998)
The quest for quality education is the mission as well aa the visionof every educational institution. This is especially true with privateschools in as much as the attracting power of the schools depend uponthe quality of their educational output. Then, the schools reowned fortheir quality attract more student than the so called "diploma mills". Inhigher education, competition is evident in terms of enrollment.Excellence in board examinations, academic contest, sports and the like.However, despite all efforts to inform quality there are still colleges anduniversities which turn out medicare graduates. Studies have been undertaken to assess the quality of Philippineeducation. One important body that undertook such study was theEducational Congressional Commission. It reported that "the quality ofPhilippine Education is declining continuously. As a mechanism toimprove higher education it was recommended that college anduniversity be made more cost-effective and curricular program morerelevant to the communities they save. In view of this situation,accrediting agencies were organized in order to encourage schools toimprove their educational services based on established criteria. Voluntary accreditation is a private initiative conceived by privateschools educators themselves who wanted to become leaders ineducation in their own right with the proper supervisior. of their ownschools in maintaining quality.
Master Thesis
Keywords: Philippine Education; Educational Congressional Commission; Guidance & Counceling